2020
DOI: 10.1038/s41598-020-62961-5
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Monotherapy for Chemotherapy-Refractory Metastatic Colorectal Cancer: A Multi-centre, Single-Arm, Prospective Study

Abstract: Angiogenesis inhibitors are of considerable interest for treating metastatic colorectal cancer (mcRc). This trial evaluated the efficacy and safety of apatinib in chemotherapy-refractory mCRC. Apatinib 500 mg was administered daily to patients who had progressed after two or more lines of standard fluorouracil-based chemotherapy. Primary endpoint was progression-free survival (PFS). Secondary endpoints were objective response rate (ORR), disease control rate (DCR), overall survival (OS), and toxicity. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 66 publications
3
45
0
Order By: Relevance
“…13 These results are corroborated by additional smaller studies in mCRC including Guo and colleagues, (PFS 3.8 months, OS not reached), Liang and colleagues, (PFS 4.8 months, OS 10.1 months), and Li and colleagues, (PFS 3.7 months, OS 7.3 months). [13][14][15][16] Adverse effects from rivoceranib were consistent with inhibitors of the VEGF pathway and included hypertension, proteinuria, and hand-foot syndrome. 3,13 A multicenter phase I/II trial is underway in the United States further evaluating the rivoceranib in mCRC (NCT04073615).…”
Section: Rivoceranib (Apatinib Yn968d1)supporting
confidence: 60%
See 2 more Smart Citations
“…13 These results are corroborated by additional smaller studies in mCRC including Guo and colleagues, (PFS 3.8 months, OS not reached), Liang and colleagues, (PFS 4.8 months, OS 10.1 months), and Li and colleagues, (PFS 3.7 months, OS 7.3 months). [13][14][15][16] Adverse effects from rivoceranib were consistent with inhibitors of the VEGF pathway and included hypertension, proteinuria, and hand-foot syndrome. 3,13 A multicenter phase I/II trial is underway in the United States further evaluating the rivoceranib in mCRC (NCT04073615).…”
Section: Rivoceranib (Apatinib Yn968d1)supporting
confidence: 60%
“…13 Additionally, rivoceranib exceeded the historical median PFS (1.7 months) and OS (6.3 months) for best supportive therapy in the third-line and beyond for mCRC. 13 These results are corroborated by additional smaller studies in mCRC including Guo and colleagues, (PFS 3.8 months, OS not reached), Liang and colleagues, (PFS 4.8 months, OS 10.1 months), and Li and colleagues, (PFS 3.7 months, OS 7.3 months). [13][14][15][16] Adverse effects from rivoceranib were consistent with inhibitors of the VEGF pathway and included hypertension, proteinuria, and hand-foot syndrome.…”
Section: Rivoceranib (Apatinib Yn968d1)mentioning
confidence: 94%
See 1 more Smart Citation
“…First, bevacizumab combined with chemotherapy is recommended as standard therapy for mCRC (3), but the impact of prior bevacizumab on later treatment is still unclear. Retrospective and prospective studies (22,23) regarding the efficacy of apatinib in mCRC revealed no significant differences between patients with or without prior treatment with bevacizumab in PFS and OS. Besides, clinical trials (10,11) evaluating the efficacy of fruquintinib did not exclude patients with previous use of bevacizumab.…”
Section: Discussionmentioning
confidence: 95%
“…These results were confirmed in the CONCUR trial (median PFS: 3.2 vs. 1.7 months, P < 0.0001; median OS: 8.8 vs. 6.3 months, P = 0.00016; respectively) (6). A recent prospective study of apatinib also showed efficacy in chemotherapy-refractory mCRC with median PFS and OS of 4.8 months (95% CI, 3.653-5.887 months) and 9.1 months (95% CI, 5.155-13.045 months), respectively (22). In the present study, we retrospectively explored the efficacy of the newly approved VEGFR inhibitor, fruquintinib, and observed shorter median PFS (3.1 vs. 3.7 months) and OS (8.6 vs. 9.3 months) compared with the FRESCO trial.…”
Section: Discussionmentioning
confidence: 96%